Cold water immersion: kill or cure? - Tipton, M. J.; Collier, N.; Massey, H.; Corbett, J.; Harper, M. (Experimental Physiology, 2017)
Like other environmental constituents such as pressure, heat and oxygen, cold water can be either good or bad, threat or treatment depending on circumstance. Given the current increase in the popularly of open cold water swimming it is timely to review the various human responses to cold water immersion (CWI) and consider the strength of the claims made for the effects of CWI. As a consequence, in this review we look at the history of CWI and examine CWI as a pre-cursor to drowning, cardiac arrest and hypothermia. We also assess its role in prolonged survival underwater, extending exercise time in the heat and treating hyperthermic casualties. More recent uses, such as in the prevention of inflammation and treatment of inflammation-related conditions are also considered. It is concluded that the evidence-base for the different claims made for CWI are varied, and whilst in most cases there seems to be a credible rationale for the benefits or otherwise of CWI, in some cases the supporting data remain at the level of anecdotal speculation. Clear directions and requirements for future research are indicated by this review.